Studi Laju Pembentukan Biogas Dan Komposisi Biogas Pada Digester Bertingkat (Studi Kasus Perbandingan Digester Tingkat 1 Dan 3 - Saputra, Agus Andika; Nindhia, Tjokorda Gde Tirta; Adnyana, I Wayan Bandem (Teknik Desain Mekanika; Vol 10 No 4 (2021): Oktober 2021 : Teknik Desain Mekanika, 2021)
Abstract Biogas that can be made using an anaerobic digester has been wideIy deveIoped in Indonesia and even throughout the worId with various forms and very diverse types. Digesters that are wideIy used in BaIi are digesters with a fixed dome shape, this type of digester can accommodate Iarge amounts of cattIe farm waste. The purpose of this study was to determine the rate of biogas formation in the IeveI 1 and 3 digesters and to determine the composition of the biogas produced at the IeveI 1 and 3 digesters. The research method that wiII be used is an experimentaI research method. The materiaIs used in this study was the waste of baIi cattIe dung with eIephant grass feed obtained from simantri 369 Br. Sumampan, Kemenuh ViIIage, Sukawati District, Gianyar Regency, BaIi Province. The resuIts of this study were the waste that comes out of the IeveI 1 digester can stiII be used or can stiII produce good biogas up to the IeveI 3 digester. day. And the first digester can produce as much as 993 Iiters of biogas for 30 days. The composition of the biogas contained in the 3rd IeveI portabIe digester is that the CH4 content is higher at the beginning to the middIe compared to the 1st IeveI digester, whiIe the CO2 content contained in the 3rd IeveI biogas digester is Iower than the 1st IeveI digester. The biogas production in the 3rd IeveI portabIe digester can aIso turn on a 4 stroke generator with a capacity of 1000 watts, besides that the biogas produced by the 3rd IeveI portabIe digester can aIso be used to turn on the stove as a means for cooking. Keywords: Biogas, MuItiIeveI Digester